2013
DOI: 10.4028/www.scientific.net/amm.357-360.732
|View full text |Cite
|
Sign up to set email alerts
|

The Study on Metakaolin's Effect of Restraining the Alkali-Silica Reaction of Slate Aggregate

Abstract: The study on metakaolins inhibit effect to alkali-silica reaction (ASR) of slate aggregate by the way of accelerated mortar-bar test (AMBT),the results show that when the gel contains 15% metakaolin,the 14d expansion ratio is less than 0.03%,the inhibit reach the wear goal. But when we add the content of metakaolin, the expansion ratios are similar at every age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…In a word, slag can't restrain ASR very well with the sandstone aggregate. And its effect is far worse than other admixture, such as silica fume, metakaolin [12].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…In a word, slag can't restrain ASR very well with the sandstone aggregate. And its effect is far worse than other admixture, such as silica fume, metakaolin [12].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Many researchers have shown that some chemical admixtures e.g. lithium compounds and supplementary cementitious materials (SCM) such as silica fume, metakaolin, blast furnace slag, fly ashes, zeolite, glass powder, ground clay brick can be used successfully to minimise the effect of ASR [3][4][5][6][7][8][9][10][11][12][13][14]. It is known that mineral additions having pozzolanic properties are capable of reducing the ASR-induced expansion.…”
Section: Introductionmentioning
confidence: 99%